SIRT1 is a transcriptional enhancer of the glucocorticoid receptor acting independently to its deacetylase activity. (5th February 2018) - Suzuki, Shigeru; Iben, James R.; Coon, Steven L.; Kino, Tomoshige
Abstract: Glucocorticoids have strong effects on diverse human activities through the glucocorticoid receptor (GR). Sirtuin 1 (SIRT1) is a NAD + -dependent histone deacetylase and promotes longevity by influencing intermediary metabolism and other regulatory activities including mitochondrial function. In this study, we examined the effects of SIRT1 on GR-mediated transcriptional activity. We found that SIRT1 enhanced GR-induced transcriptional activity on endogenous and exogenous glucocorticoid-responsive genes, whereas knockdown of SIRT1 attenuated it. This effect of SIRT1 was independent to its deacetylase activity, as the SIRT1 mutant defective in this activity (H363Y) enhanced GR transcriptional activity, and the compounds inhibiting or activating the SIRT1 deacetylase activity did not influence it. RNA-seq analysis revealed that SIRT1 knockdown influenced ∼30% of the glucocorticoid-responsive transcriptome for most of which it acted as an enhancer for positive/negative effects of this hormone. SIRT1 physically interacted with GR, and was attracted to GR-bound glucocorticoid response elements in a glucocorticoid-dependent fashion. SIRT1 cooperatively activated GR transcriptional activity with the PPARγ coactivator-1α also in its deacetylase activity-independent fashion. Thus, SIRT1 is a novel transcriptional enhancer of GR-induced transcriptional activity possibly by functioning as a scaffold for the transcriptional complex formed on GR. Highlights: SIRT1 enhances glucocorticoid receptor (GR) transcriptional activity. This activity augments both transactivating and transrepressing actions of GR. The activity is independent to its deacetylase activity. SIRT1 physically interacts with GR bound on the glucocorticoid response elements.